Clinical review: Extracorporeal membrane oxygenation - Gattinoni, Luciano (BioMed Central, 2011)
The H1N1 flu pandemic led to a wider use of extracorporeal membrane oxygenation (ECMO), proving its power in hypoxemic emergencies. The results obtained during this pandemic, more than any randomized trial, led to the worldwide acceptance of the use of membrane lungs. Moreover, as centers that applied this technique as rescue therapy for refractory hypoxemia recognized its strength and limited technical challenges, the indications for ECMO have recently been extended. Indications for veno-venous ECMO currently include respiratory support as a bridge to lung transplantation, correction of lung hyperinflation during chronic obstructive pulmonary disease exacerbation and respiratory support in patients with the acute respiratory distress syndrome, possibly also without mechanical ventilation. The current enthusiasm for ECMO in its various aspects should not, however, obscure the consideration of the potential complications associated with this life-saving technique, primarily brain hemorrhage